CPI-613 rewires lipid metabolism to enhance pancreatic cancer apoptosis via the AMPK-ACC signaling - Gao, Lixia (J Exp Clin Cancer Res, 2020)
BACKGROUND: Pancreatic cancer remains one of the most rapidly progressive and deadly malignancies worldwide. Current treatment regimens only result in small improvements in overall survival for patients with this cancer type. CPI-613 (Devimistat), a novel lipoate analog inhibiting mitochondrial metabolism, shows the new hope for pancreatic cancer treatment as an efficient and well-tolerated therapeutic option treated alone or in combination with chemotherapy. METHODS: Pancreatic cancer cells growing in planar 2D cultures and 3D scaffold were used as research platforms. Cell viability was measured by MTT and alamarBlue, and apoptosis was assessed by JC-1 staining and flow cytometry with Annexin V-FITC/PI staining. The mechanism behind CPI-613 action was analyzed by western blot, transmission electron microscopy, and lipolysis assay kits, in the presence or absence of additional signaling pathway inhibitors or gene modifications. RESULTS: CPI-613 exhibits anticancer activity in pancreatic cancer cells by triggering ROS-associated apoptosis, which is accompanied by increased autophagy and repressed lipid metabolism through activating the AMPK signaling. Intriguingly, ACC, the key enzyme modulating lipid metabolism, is identified as a vital target of CPI-613, which is inactivated in an AMPK-dependent manner and influences apoptotic process upon CPI-613. Blockade or enhancement of autophagic process does not increase or blunt apoptosis to CPI-613, but inhibition of the AMPK-ACC signaling significantly attenuates apoptosis induced by CPI-613, suggesting CPI-613-mediated lipid metabolism reduction contributes to its cytotoxicity in pancreatic cancer cells. CONCLUSIONS: These findings explore the critical role of lipid metabolism in apoptosis, providing new insights into the AMPK-ACC signaling axis in crosstalk between lipid metabolism and apoptosis in CPI-613 treatment.